2022
DOI: 10.1038/s41598-022-26237-4
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic screening for osteoporosis using hydroxyapatite measurements of the vertebral by thorax dual-energy spectral CT in postmenopausal females

Abstract: The purpose of this study was to evaluate the feasibility of opportunistic screening for osteoporosis in postmenopausal females using the dual-energy CT(DECT)-derived hydroxyapatite (HAP) concentration and CT value of L1-vertebra. 239 consecutive postmenopausal female patients were enrolled and underwent both chest DECT and Dual energy X-ray absorptiometry (DXA). According to the T-score of the 1st lumbar vertebra on DXA, patients were divided into the osteoporosis group (T $$\le$$ ≤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Some experimental and clinical studies indicate that the density value of the base substance can effectively represent the material content when the chosen base material pairs closely match the actual material. Similar to the findings of Deng et al, we found that the HAP concentration using the HAP-fat material pair was correlated with BMD, and the CT value (HU) was also measured on the DECT monochromatic images that are less susceptible to beam hardening artifacts [24].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Some experimental and clinical studies indicate that the density value of the base substance can effectively represent the material content when the chosen base material pairs closely match the actual material. Similar to the findings of Deng et al, we found that the HAP concentration using the HAP-fat material pair was correlated with BMD, and the CT value (HU) was also measured on the DECT monochromatic images that are less susceptible to beam hardening artifacts [24].…”
Section: Discussionsupporting
confidence: 88%
“…DXA may introduce variability in measurements due to overlying soft tissues, vascular calcifications, intestinal contents, and degenerative bone changes, potentially influencing results. Similar to other studies in the literature, we chose to focus exclusively on the evaluation of the trabecular component to avoid the potential for a false increase in BMD values due to the causes mentioned above [24,25]. Additionally, trabecular bone is more susceptible to involution in osteopenic or osteoporotic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Wesarg et al [19] investigated localized force measurements in 29 cadaveric specimens and found a strong correlation between DECT and DXA in quantifying local bone density. Another study involving 239 postmenopausal female patients [20] indicated a moderate-to-high correlation between Hounsfield attenuation profile (HAP) and CT values of the first lumbar vertebra with BMD obtained through DXA (HAP, R = 0.614; CT value, R = 0.625; all P < .01). Therefore, DECT can employ post-image processing techniques, such as material separation imaging and virtual monoenergetic imaging, to quantitatively assess vertebral bone density, facilitating the measurement of bone mass reduction and the diagnosis of OP.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, many studies note that DXA scanning is an underutilized technique, with screening rates as low as 30% in Medicare patients [59]. Further, there are many limitations to traditional DXA scanning, as overlying tissue, bowel contents, and vascular calcifications can yield variations in BMD values [60]. Although quantitative CT (QCT) has also been used to evaluate BMD, this technique is costly, affected by marrow adipose tissue, and provides higher radiation-dose exposure than DXA scanning [61].…”
Section: Osteoporosismentioning
confidence: 99%
“…Yet, there is currently mixed data on the accuracy of DECT in the assessment of BMD. Certain studies state that DECTassociated HAP values moderately correlate with DXA images (r = 0.614) while others report linear correlations (r = 0.97) [60,63]. Yet, it is imperative to note that the latter study used a phantom setup and has yet to validate their methods in a clinical setting.…”
Section: Osteoporosismentioning
confidence: 99%